Penggunaan Kecerdasan Buatan (AI) dan ChatGPT dalam Konteks Pembelajaran Bahasa Inggris: Persepsi Mahasiswa dan Tantangannya: Pemanfaatan Kecerdasan Buatan dan ChatGPT dalam Pembelajaran Bahasa Inggris: Persepsi dan Tantangan Siswa - Nur Hasanah; Nur Aini Syah (Language Development Center, 2025)
Background: The use of Artificial Intelligence (AI) technologies in teaching and learning at universities is unavoidable trend in the Industry 4.0 age. This study uniquely integrates the 5E learning model with ChatGPT in a real EFL classroom context, which is till underexplored in Indonesian tertiary education. Purpose: The aims of this research are to investigate students’ perception and experience of using AI technology application in English Classes and their challenges. It focuses on the influence of ChatGPT in the five aspects of 5E learning, namely engagement, exploration, explanation, elaboration, and evaluation, which were analyzed from questionnaire and interview. Method: The Students having experience using chat GPT of General English class at the second semester in State Islamic University Ponorogo took part in this study. This study employed mixed methods (quantitative and qualitative research approach), with data being gathered via questionnaire and interview. Results and Discussion: The finding based on students’ perception indicate that artificial intelligence can be an effective tool to aid student in English teaching and learning process. The students showed positive view of ChatGPT (M=2,7-3,02) in the learning process, including in the 5E learning model. The students felt that ChatGPT helped to increase their engagement and enthusiasm for learning English. ChatGPT not only facilitates understanding and build English language skill but also provides an interesting and interactive learning experience. However, some students meet challenges such as limiting access, signal strength, inaccurate answers, and a lack of prompts. Another challenge is AI can make some students feel lazy to learn and depend on AI tools. Conclusions and Implications: It is suggested that using AI should be followed by prompt formulation training and be done by considering other reference sources both books and journals and should be balanced with human interaction in Language Learning. By comparing several reference sources and interacting with humans, it will help students gain a broader perspective and avoid laziness of thinking and dependence on AI.